EVALUATION OF VILLAGE GOVERNMENT POLICY ON POVERTY ALLEVIATION IN KWALA SERAPUH VILLAGE, TANJUNG PURA DISTRICT, LANGKAT REGENCY - Risky Hamdani; Kariaman Sinaga; Rahman Tahir (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Poverty is a multidimensional social problem that remains a major challenge in development, particularly in rural areas. As the frontline of local government, village authorities play a strategic role in formulating and implementing poverty alleviation policies that match local needs. This study aims to evaluate the policies of the Kwala Serapuh Village government in addressing poverty, focusing on the form of policies, the implementation process, the effectiveness of policies, and the supporting and inhibiting factors of implementation. The study uses a qualitative approach with a descriptive case-study method. Data were collected through in-depth interviews, field observation, and document studies involving village officials, the Village Consultative Body (BPD), village facilitators, community leaders, and beneficiary residents. Data were analysed using the interactive model of Miles and Huberman through data reduction, data presentation, and conclusion drawing. The findings show that poverty alleviation policies in Kwala Serapuh have been moderately effective in supporting the basic needs of poor households through social assistance programmes, particularly the Direct Cash Assistance from Village Funds (BLT-DD) and basic infrastructure development. However, the policies have not fully addressed the structural roots of poverty, such as the absence of stable income and limited access to economic resources. Supporting factors include the commitment of village officials, the support of BPD, and the role of village facilitators. Inhibiting factors include limited human-resource capacity, inaccurate poverty data, and suboptimal community participation. Strengthening empowerment-based policies is therefore essential for sustainable poverty alleviation at the village level. Keywords: Policy Evaluation; Village Government; Poverty Alleviation; Village Fund; Kwala Serapuh Village